Dance Therapy terhadap Penurunan Kecemasan pada Pasien Kanker - Many Flora; Saima Putri Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effectiveness of dance therapy on anxiety in cancer patients. This research method used a systematic review conducted through the PubMed, ScienceDirect, and ProQuest databases using the keywords